2021
DOI: 10.1186/s12906-021-03402-2
|View full text |Cite
|
Sign up to set email alerts
|

Anti-dengue activity of super critical extract and isolated oleanolic acid of Leucas cephalotes using in vitro and in silico approach

Abstract: Backgrounds Leucas cephalotes is a common ethnomedicinal plant widely used by traditional healers for the treatment of Malaria and other types of fever. Oleanolic acid and its derivatives have been reported for various types of pharmacological activities, such as anti-inflammatory, antioxidant, anticancer, hepatoprotective, anti-HIV and anti-HCV activity. Methods L.cephalotes plant extracts were prepared by supercritical fluid extraction (SFE) meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…The WHO reported that about 80% of people in developing countries rely on traditional drugs for their primary health care needs [ 82 ]. About 855 traditional medicines used in the world are obtained from crude plant extracts [ 83 ].…”
Section: Treatmentmentioning
confidence: 99%
“…The WHO reported that about 80% of people in developing countries rely on traditional drugs for their primary health care needs [ 82 ]. About 855 traditional medicines used in the world are obtained from crude plant extracts [ 83 ].…”
Section: Treatmentmentioning
confidence: 99%
“…An in-depth knowledge of the chemical composition of plants allows for a more accurate appraisal of their potential and medical worth. There are many factors that contribute to the success of the transition of a bioactive molecule into a commercially viable pharmaceutical in recent decades [ 90 , 91 ]. This can be done with the help of cutting-edge technology and well-established techniques.…”
Section: Reviewmentioning
confidence: 99%
“…As no drugs and vaccines are available for these vector-borne viruses like dengue, Zika and Chikungunya viruses, Ethnomedicine is gaining interest because of its safety and broadspectrum activity over synthetic drugs. Medicinal plants already play a significant role in controlling various viral infections of Herpes Simplex Viruses, Dengue, Chikungunya [38][39][40][41][42][43][44]. Nowadays, vector-borne diseases increasing vigorously, which causes economic and social disturbances?…”
Section: Future Approachesmentioning
confidence: 99%